Multi–objective optimization of high oleic sunflower oil and monoglycerides oleogels: Searching for rheological and textural properties similar to margarine - Palla, Camila Andrea (2017)
Different processing conditions to obtain oleogels from high oleic sunflower oil and Myverol were explored with the aim to develop a fat with similar rheological and textural characteristics to margarine. The effects of the concentration of Myverol (MV), the mixture preparation temperature (TP), the speed of agitation (SA) and the ambient cooling temperature (TC) on 10 different selected responses - the oil binding capacity and the most representative rheological and textural parameters - were analyzed by applying an incomplete factorial design of four factors with three levels. In general, the MV and TC variables were the most significant factors on each analyzed response. The oleogel obtained under multi-objective optimization conditions achieved the same hardness value of margarine and similar parameters of the rheological models, whereas the adhesiveness and cohesiveness values were not totally reached. Likewise, their ability to retain oil was 98.45%, indicating the formation of a desirable strong gel network.